Respuesta :

fnyaba

Answer: a. -3(x+1), b. 19-3x, c. -9 and d. 13

Step-by-step explanation:

Lets begin with a.  (fog)(x)=f(g(x))

                                             =f(2x+x+7), Note that 2x+x+7=3x+7

                                             =f(3x+7) (where there  is x if the function f(x) we

                                               substitute x by 3x+7)

                                             =4-(3x+7) =4-3x-7=-3x-3= -3(x+1).

                            b. (gof)(x)=g(f(x))=g(4-x) (where there is x in the function  

                                                g(x) we substitute with 4-x)

                                             = 3(4-x)+7 = 19-3x

                          c.  (fog)(2) = -3(2+1) = -9 (we now substitute x with 2 in -3(x+1). )

                           d. (gof)(2) = 19-3(2)=19-6=13. (Again we now substitute x with

                                               2 in 19-3x)